The Effectiveness of Extensive Reading on Students’ Reading Comprehension Achievement as Observed from Students’ Motivation - Sarwo Edy (Pascasarjana UM, 2014)
Abstract: The study investagates if the extensive reading activity is effective in improving students’ reading comprehension achievement and if there is any interaction between the extensive reading and the students’ reading motivation.This study employs a quasi-factorial design with a pretest and posttest non-equivalence group design. The subjects of the study were the second semester students of STAIN Curup, Bengkulu in academic year 2011-2012. Students’ reading comprehension achievement was measured by an objective test in the form of multiple choices; students’ reading motivation was profiled and classified by a reading motivation questionnaire. In analyzing the data collected, the re-search used Multivariate Analysis of Covariance. This research reveals the following findings. (1) The students taught by the extensive reading activity showed higher scores than those taught by conventional way. (2) There is no interaction between students’ motivation and extensive reading. Key Words: extensive reading, reading comprehension, effectiveness Abstrak: Studi ini meneliti apakah kegiatan membaca ekstensif efektif meningkatkan prestasi siswa dalam memahami bacaan dan apakah ada interaksi antara membaca ekstensif dan motivasi membaca siswa. Penelitian ini menggunakan quasi-factorial design dengan pre test dan posttest non-equiva-lence group design. Subjek penelitian adalah mahasiswa semester II STAIN Curup, Bengkulu tahun ajaran 2011-2012. Prestasi pemahaman siswa membaca diukur dengan tes objektif dalam bentuk pilihan ganda; motivasi membaca siswa digambarkan dan diklasifikasikan dengan kuesioner motivasi membaca. Analisis data penelitian menggunakan multivariat analisis kovarians. Hasil penelitian adalah sebagai berikut. (1) Siswa yang dibelajarkan dengan kegiatan membaca ekstensif menunjukkan skor yang lebih tinggi daripada yang dibelajarkan dengan cara konvensional. (2) Tidak ada interaksi antara motivasi belajar siswa dengan membaca ekstensif. Kata kunci: membaca ekstensif, pemahaman bacaan, efektivitas